CHEMICAL COMPOSITION AND AMINO ACIDS CONTENT OF FIVE SPECIES OF EDIBLE GRASSHOPPERS FROM MEXICO - Ruiz, Virginia Melo; Sandoval-Trujillo, Horacio; Quirino-Barreda, Tomas; Sánchez-Herrera, Karina; Díaz-García, Rafael; Calvo-Carrillo, Concepción (Emirates Journal of Food and Agriculture, 2015)
Food security is the main concern of government due to malnutrition worldwide. The aim of this study was to assess macronutrients and amino acids in five species of grasshoppers, consumed in rural and urban communities. Samples were captured in different agro climatic environment conditions, wherever vegetation grows, and the macronutrients were raw, analyzed in dry basis by the AOAC methods and amino acids by cation exchange chromatography. The obtained data showed a high protein content, ranging from 70% to 75%; lipids 4% to 6%; minerals 3% to 5%; fiber 6% to 8% and soluble carbohydrates 6% to 18%, including essential amino acids that play an important role in human metabolism, with tryptophan as limiting factor. The different species of the studied grasshoppers are high in proteins, essential macromolecules for human life that decrease protein-energy malnutrition; the excess of amino acids after releasing the amino group will provide energy, as well as soluble carbohydrates. They also have minerals that are needed to prevent anemia, and fiber, non-digestible carbohydrates essential in a healthy diet. In conclusion, the daily consumption of 5 or 6 grasshoppers is a good source of nutrients that will provide optimal health to population.